Perancangan Destination Branding Sebagai Sarana Desa Pariwisata Dan Budaya - Zellita Aprilhani Suparyono; Nisa Eka Nastiti; Olivine Alifaprilina Supriadi (Universitas Telkom, 2024)
Indonesia’s cultural diversity is enormous, not only culture but history, and also united customs. Jelekong Arts Village is avillage in Bandung Regency which has an abundance of cultural and artistic diversity, the people of Jelekong themselveshave also been trained in arts that have been passed down from generation to generation. Examples of culture and art in theJelekong Art Village include painting craftsmen, Wayang Golek craftsmen, and even Wayang Golek performances. However,unfortunately, interest in visitors to the Jelekong Art Village has greatly decreased and the people there do not have strongand interesting information media, so that many Jelekong people have not continued their culture and art and there are stillmany people from Bandung and outside Bandung who do not know about the Jelekong Art Village. With this, the researchthat has been carried out uses a qualitative method which is based on the theory of Visual Communication Design byobtaining data through observation activities, surveys, question and answer activities with the Jelekong community andliterature regarding the Jelekong Art Village. With the final result in the form of destination branding as an informationmedium for the Jelekong Arts Village so that the people of Bandung and also outside Bandung have an interest in theJelekong Arts Village and have a lot of curiosity about the Jelekong Arts Village.